Design, build and test of a novel X-shaped, tilt-wing quadcopter - Van Deventer, Dewald (Stellenbosch : Stellenbosch University, 2025)

(untitled)
van Deventer, D. 2025. Design, build and test of a novel X-shaped, tilt-wing quadcopter. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/20324f4d-107a-46b0-8f03-6b6e8b989207